Geopolitical Risks and Equity Returns: Does Size Matter? - Kunjal, Damien (The Journal of Accounting and Management, 2025)
In recent years, geopolitical risks and uncertainties have increasingly disrupted financial markets by introducing vulnerabilities that affect equity investment decisions, with firm size playing a critical role in determining resilience to such shocks. This study investigates the size-specific effects of GPR on equity returns across different market conditions. To achieve the objectives of this study, size-based JSE indices are employed as proxies for firms of varying capitalisations, in conjunction with the global and country-specific GPR indices developed by Caldara and Iacoviello (2022), covering the period from 1 May 2015 to 30 April 2025. A Markov Regime-Switching model is used to distinguish between bull and bear market regimes. The analysis yields three key findings: (I) the effects of domestic and global GPR are not uniform, (II) equity return sensitivity to GPR shocks is regime-dependent, and (III) the impact of GPR varies across firm sizes. These findings underscore the importance of a multidimensional approach to risk management, whereby investors and policymakers should consider both firm size and prevailing market regimes when assessing exposure to geopolitical risk.